Healing defects in armchair graphene nanoribbons for enhanced charge transport - Lindenthal, Sebastian; Sebastian, Finn; Herrmann, Niklas; Zorn, Nicolas; Zaumseil, Jana (ACS applied nano materials, 2025)
Graphene nanoribbons (GNRs) are promising carbon-based nanomaterials for next-generation nanoelectronic devices. However, their synthesis (in-solution or on-surface) is not perfect and the impact of defects in the sp2 carbon lattice of GNRs on their charge transport properties is not yet fully understood. Here, we investigate the influence of lattice defects on the macroscopic charge transport in thin films of solution-synthesized 9-armchair GNRs (9-aGNRs) with intrinsic edge defects. The density of these edge defects could be reduced by thermal annealing at 260-300 °C in inert atmosphere, which is proposed to induce postsynthetic cyclization. The decreasing number of defects with annealing time and temperature was corroborated by absorption spectroscopy and a decreasing D/G Raman mode ratio while the film morphologies remained unaltered. Annealed 9-aGNR films showed ambipolar charge transport characteristics in electrolyte-gated transistors with significantly higher on-currents, transconductances and on/off-ratios for both hole and electron transport compared to films that were annealed below the temperature required for defect healing. Consequently, defect healing by annealing in inert atmosphere should be a key step in GNR device processing to achieve optimal charge transport.
Gesehen am 21.10.2025